Enhanced SVPWM Techniques for Six-Phase Inverters: Mitigation of Current Harmonics and Common Mode Voltage - Kotb B. Tawfiq; Hatem Zeineldin; Ahmed Al-Durra; Ehab F. El-Saadany (IEEE Open Journal of the Industrial Electronics Society)
Reducing current harmonics and common mode voltage (CMV) holds highest importance for six-phase electric vehicles, as it not only prolongs the lifespan of crucial components but also significantly enhances overall vehicle performance, operational efficiency and improved thermal management. This article introduces an innovative switching sequence for space vector pulsewidth modulation (SVPWM) in six-phase inverters, aimed at significantly reducing CMV and total harmonic distortion (THD) of phase currents. The proposed method optimally selects switching states with minimal and/or zero CMV and ensures balanced distribution in the $x - y$ subspace, resulting in null $x - y$ voltage and current components. Comparative analysis was conducted against two existing SVPWM techniques: reference SVPWM sequence-1 (RSVM1), known for the lowest THD but highest CMV, and six-phase discontinuous CMV sequence-2-A2 (6Φ-DCMV2-A2), which has the lowest CMV but higher THD. Experimental setups and MATLAB simulations validated the findings. The proposed SVPWM demonstrates a CMV reduction of 23.86% and 89.42% compared to RSVM1 at modulation indices of 0.9 and 0.1, respectively. It also achieves the lowest THD, being 16.67% and 36.72% lower than 6Φ-DCMV2-A2 for asymmetrical six-phase induction motors and R-L load, respectively. Furthermore, the three SVPWM techniques showed comparable conduction, switching, and overall inverter losses.